2007
DOI: 10.1203/pdr.0b013e3180db2949
|View full text |Cite
|
Sign up to set email alerts
|

New Insights in the Etiology and Pathophysiology of Irritable Bowel Syndrome: Contribution of Neonatal Stress Models

Abstract: Irritable bowel syndrome (IBS) is one of the most common gastrointestinal disorders, characterized by abdominal pain and disturbed defecation that cannot be explained by structural abnormalities. Although IBS symptoms (visceral pain, increased gut permeability, motility alterations) are clearly established, the etiology of this pathology is loosely understood. Nevertheless, clinical studies have reported that some early abuse (physical and psychological) is often associated with IBS development. Thus, loss and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
136
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 146 publications
(141 citation statements)
references
References 77 publications
3
136
0
2
Order By: Relevance
“…In a variety of stress related IBS models, MS of newborn rats is considered to be a well-established model of early life stress induced visceral hypersensitivity. 7 In 2002, Coutinho et al 5 showed that maternal separated Long-Evans rats suffered from stressinduced visceral hyperalgesia and increased colonic motility, which could mimic IBS in humans. To date, accumulating animal experiments 16 confirm that neonatal MS could induce visceral hyperalgesia in adult rats, suggesting early life adverse events can strengthen neural responses to visceral nociceptive stimulus in adulthood.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In a variety of stress related IBS models, MS of newborn rats is considered to be a well-established model of early life stress induced visceral hypersensitivity. 7 In 2002, Coutinho et al 5 showed that maternal separated Long-Evans rats suffered from stressinduced visceral hyperalgesia and increased colonic motility, which could mimic IBS in humans. To date, accumulating animal experiments 16 confirm that neonatal MS could induce visceral hyperalgesia in adult rats, suggesting early life adverse events can strengthen neural responses to visceral nociceptive stimulus in adulthood.…”
Section: Discussionmentioning
confidence: 99%
“…23,24 Animal studies also found that early life stressful events such as MS in the rodent can cause disruption of the HPA axis. 7,25,26 Early life stress can influence development of the HPA axis, as well as regulation of satiety-related hormones, leptin, insulin, and ghrelin, again influencing appetite, feeding behavior, and metabolism, which results in the development of obesity. 27 The weight of MS rats can gradually return to normal level on PND56, suggesting that the harmful effect of MS on weight can be improved in rat adulthood after normal feeding.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…1,2 In preclinical studies, rodents raised under conditions of intermittent maternal separation develop features of IBS-like manifestations and alterations in behavior when they are adults. [3][4][5][6] Another model of early-life adverse events is the rearing of pups by dams subjected postpartum to conditions of limited bedding and nesting stress. 7,8 This model has face validity in humans 7,8 where the mother is continuously present but provides an altered repertoire of maternal behaviors indicative of fragmented and erratic care 9 and altered dam-pup interactions.…”
Section: Introductionmentioning
confidence: 99%